Distortions in sound: Bridging acoustics and psychoacoustics in auditory perception - Tauhid Firman Nurdin (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2024)
The field of acoustics encompasses the examination of sound, encompassing both its physical characteristics and the way in which humans perceive auditory input. Acoustics is the study of how sound waves are created and spread physically, while psychoacoustics connects these physical characteristics to our auditory perceptions. Comprehending these two features is essential for progress in audio technology and understanding auditory perception aberrations such as paracusia and diplacusis. This research consolidates information from multiple investigations to examine the interaction between acoustics and psychoacoustics. The technique entails examining the current body of literature on the fundamental principles governing sound waves, their interaction with various materials, and their movement across space. The examination of psychoacoustic elements involved the conversion of sound waves into brain impulses. The study also examines certain psychoacoustic phenomena, such as the sense of pitch and auditory distortions. By combining acoustic and psychoacoustic concepts, we can gain a thorough comprehension of how we perceive sound. Sound waves, generated by mechanical vibrations, pass through substances such as air, causing compression and rarefaction cycles that move at a speed of about 344 m/s at a temperature of 20°C. Psychoacoustics studies the perception of sound waves, specifically how they are processed by the ear and converted into neural signals that the brain can understand. The key findings reveal the subjective nature of pitch perception, where alterations in intensity or length impact the perceived frequency and the precise sensitivity of pitch discrimination. Furthermore, abnormalities such as paracusia and diplacusis emphasize the intricacies of auditory perception. The study highlights the significance of psychoacoustics in audio technology, where principles are utilized in audio compression and noise reduction to improve sound quality and clarity. The comprehensive comprehension of acoustics and psychoacoustics lays the groundwork for advancements in audio technology and the creation of auditory experiences.